2004
DOI: 10.1073/pnas.0307195101
|View full text |Cite
|
Sign up to set email alerts
|

The evolution of a pleiotropic fitness tradeoff in Pseudomonas fluorescens

Abstract: The evolution of ecological specialization is expected to carry a cost, due to either antagonistic pleiotropy or mutation accumulation. In general, it has been difficult to distinguish between these two possibilities. Here, we demonstrate that the experimental evolution of niche-specialist genotypes of the bacterium Pseudomonas fluorescens that colonize the air-broth interface of spatially structured microcosms is accompanied by pleiotropic fitness costs in terms of reduced carbon catabolism. Prolonged selecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
168
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 160 publications
(178 citation statements)
references
References 34 publications
9
168
0
1
Order By: Relevance
“…We demonstrate a significant negative association between relative fitness (w) during growth and survival (su) in the Com+ and Com − groups, strongly suggesting antagonistic pleiotropy between the traits responsible for 'early' and 'late' performance in the 90 h passage. Previous reports on antagonistic pleiotropy in bacteria demonstrate a role in ecological specialization (Cooper and Lenski, 2000;Cooper et al, 2001;MacLean et al, 2004;Ostrowski et al, 2005;Maharjan et al, 2012). Our data suggest a previously unrecognized interplay between antagonistic pleiotropy and recombination mediated by natural transformation in bacteria.…”
Section: Discussionsupporting
confidence: 59%
“…We demonstrate a significant negative association between relative fitness (w) during growth and survival (su) in the Com+ and Com − groups, strongly suggesting antagonistic pleiotropy between the traits responsible for 'early' and 'late' performance in the 90 h passage. Previous reports on antagonistic pleiotropy in bacteria demonstrate a role in ecological specialization (Cooper and Lenski, 2000;Cooper et al, 2001;MacLean et al, 2004;Ostrowski et al, 2005;Maharjan et al, 2012). Our data suggest a previously unrecognized interplay between antagonistic pleiotropy and recombination mediated by natural transformation in bacteria.…”
Section: Discussionsupporting
confidence: 59%
“…The trade-off theory predicts that traits that promote fitness in one environment may cause a poor performance in other environments (3,9,17,20,36) and lead to specialization for either habitat. Yet, it has been argued that symbiotic rhizobia spend so much time in the soil that they should be as well adapted to the soil environment as nonnodulating strains (12).…”
Section: Discussionmentioning
confidence: 99%
“…Antagonistic pleiotropy is evident amongst mutations selected during experimental evolution of bacteria in different environments (Cooper and Lenski, 2000;MacLean et al, 2004); individual mutations with these effects are beginning to be identified (King et al, 2004;Maharjan et al, 2013). For example, a mutation resulting in antagonistic pleiotropy can alter the trade-off between self-preservation and nutritional competence (SPANC) balance (Ferenci, 2005).…”
Section: Introductionmentioning
confidence: 99%